Photoelectrochemical performance of N-doped ZnO branched nanowire photoanodes. Issue 10 (October 2017) - Allami, Shrok; Abid Ali, Zainab D.; Li, Ying; Hamody, Hayder; Jawad, Basher Hasan; Liu, Li; Li, Tianshu
Abstract: A ZnO branched-nanowire (BNW) photoanode was doped with N for use in a photoelectrochemical cell (PEC) to generate H2 from water splitting. First, ZnO BNWs were synthesized by chemical bath deposition method. Two experimental methods were used for N-doping: the time-controlled direct-current glow discharge plasma (DCGDP) and the DC magnetron plasma (DCMP) methods, to optimize N-doping of the NW structure. X-ray photoelectron spectroscopy (XPS) provided the N distribution and atomic percentage in the BNWs. The XPS results confirmed that N distribution into ZnO BNWs occurred by N substitution of O sites in the ZnO structure and through well-screened molecular N2 . The morphologies and structures of the fabricated nanostructures were investigated by field-emission scanning electron microscopy and X-ray diffraction respectively. The photoanode performance was demonstrated in photoelectrochemical studies at various power densities under both dark and illuminated conditions. Increasing the N amount in the ZnO BNWs increased the photocurrent in the PEC.